PP.08.01: AORTIC STENOSIS INFLUENCES THE RELATIONSHIP BETWEEN HYPERTENSION AND CHRONIC RENAL FAILURE. (June 2015) - Malatino, L.; Platania, I.; Tomasello, S.D.; Boukhris, M.; Cilia, C.; Terranova, V.; Di Marca, S.; Pisano, M.; Mastrosimone, G.; Cataudella, E.; Stancanelli, B.
Abstract : Objective: It is well recognized that hypertension is a major risk factor for chronic renal disease (CKD). However, whether hypertension maintains its pathogenetic role in the development of CKD in elderly patients with aortic stenosis remains circumstantial. The aim of this study was to evaluate the impact of hypertension in the development of CKD in presence of aortic stenosis. Design and method: This is a prospective study on patients older than 65 years, hospitalized in the Department of Internal Medicine in 2013. Pre-specified exclusion criteria were: acute renal failure, pulmonary embolism, recent stroke and previous procedures for aortic valvular disease. Laboratory and clinical parameters were recorded. All patients underwent a transthoracic 2D-echocardiography. Renal function was assessed using CKD-EPI formula and classified according the National Kidney Foundation criteria. Statistical analysis was performed by SPSS software (version 13.0). Results: A total of 346 patients were included in the study (age 79.5 ± 7.4 yrs): 104/346 were diabetics, 298 had mild to moderate hypertension; 59/346 showed aortic stenosis (moderate: 52; severe: 7, respectively). In absence of aortic stenosis (n = 287), eGFR resulted < 60 ml/min in 250 patients and hypertension was significantly associated with a eGFR < 60 ml/min (hypertensives: 123/250, 49%; normotensives: 13/37, 35%, P < 0.05). In patients with aortic stenosis (n = 59) eGFR resulted < 60 ml/min in 40 patients. In these patients the association with eGFR < 60 ml/min resulted similar in hypertensives (33/48, 69%) and normotensives (7/11, 64%, NS). Conclusions: Our results show that in elderly patients aortic stenosis influences the association between hypertension and CKD.